Association between hysterectomy status and stroke risk and cause-specific and all-cause mortality: evidence from the 2005–2018 National Health and Nutrition Examination Survey - Shen, Ruihuan; Wang, Jia; Tian, Yuqing; Wang, Rui; Guo, Peiyao; Shen, Shuhui; Liu, Donghao; Zou, Tong (Frontiers in Neurology, 2023)
Background Prior research on women who had hysterectomies has shown mixed results on whether or not hysterectomies increased the incidence of stroke and cause-specific or all-cause mortality. Methods Using information from the Continuous National Health and Nutrition Examination Survey (NHANES) in the United States, including linked mortality follow-up files available for public access, a multicycle cross-sectional design mortality linkage study was performed. Results Conducted during the years 2005–2018, the study sample included 14,214 female participants ranging in age from 20 to 85 years. The relationship between the hysterectomy status and the risk of stroke and cause-specific and all-cause mortality was examined using a series of weighted logistic regressions and Cox proportional hazards regressions, respectively. The presence of a hysterectomy was consistently linked to an elevated risk of stroke using weighted logistic regression models. The hysterectomy status, however, consistently showed no effect on survival by adjusted weighted Cox regression analysis. Conclusion Our study found a significant association between hysterectomy and stroke, even after adjusting for other factors that could impact risk, such as the American Heart Association (AHA)'s Life's Simple 7 cardiovascular health score and variables of age, ethnicity, marital status, income, education, and depression severity.